Buried giant - Ishiguro, Kazuo (Faber & Faber, 2015)
The Buried Giant begins as a couple, Axl and Beatrice, set off across a troubled land of mist and rain in the hope of finding a son they have not seen in years. They expect to face many hazards -- some strange and other-worldly -- but they cannot yet foresee how their journey will reveal to them dark and forgotten corners of their love for one another.